CARCASS CHARACTERISTICS OF BALI PIGS FED A CHICKEN FARM WASTE PROTEIN CONCENTRATE DIET - I K. A., Saputra; Ariana, I N. T.; Oka, A. A. (Jurnal Peternakan Tropika; Vol 12 No 4 (2024): Vol. 12 No. 4 Tahun 2024; July - August, 2024)
The study explores the characteristics of Balinese pig carcasses given food containing protein concentrate from chicken nutmeg (KPLA). The study was carried out for 2 weeks a month in the Jimbaran Bukit Cage Farm at Udayana University. RAL consists of details of the study, starting from 3 actions in total, then 5 repetitions in total. The three treatments consisted of T0: 24% CP.152 without KPLA (Control), T1: 12% CP.152 ± 12% KPLA, and T2: 24% KPLA without CP.152. His studies produced results slaughter weight and carcass weight in the T1 treatment was 39.14 ± 1,335 kg with a carcass weight of 18.89 ± 1,159 kg. The carcass percentage in the T0 treatment was 48.76 ± 1,555% and the carcass length in the T2 treatment was 44.75 ± 1,106 cm, which was largest than other nurses. Summary substitution of commercial concentrate with 12% CP.152 ± 12% KPLA produced characteristics of Bali pigs with the same slaughter weight and carcass weight as the control treatment.